2022
DOI: 10.3390/molecules27207087
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Jinhua Ham Classification Method Based on Volatile Flavor Substances and Determination of Key Odor Biomarkers

Abstract: Jinhua ham is a traditional cured meat food in China. For a long time, its grade has mainly been evaluated by the human nose through the three-sticks method, which is highly subjective and is not conducive to establishing evaluation standards through odor markers. In this paper, we analyzed the well-graded Grade I–III hams provided by Jinzi Ham Co., Ltd. (Jinhua, China). Firstly, we used different extraction fibers, extraction temperatures, and extraction time to determine the optimal conditions for headspace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… d Odor threshold taken from ( Duppeti, Kempaiah, & Manjabhatta, 2022 ). e Odor threshold taken from ( Xu, Shui, Chen, Ma, & Feng, 2022 ). f Odor threshold taken from ( Huang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… d Odor threshold taken from ( Duppeti, Kempaiah, & Manjabhatta, 2022 ). e Odor threshold taken from ( Xu, Shui, Chen, Ma, & Feng, 2022 ). f Odor threshold taken from ( Huang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al found, by studying plant substrates during drying, that hexanal and 2-methyl-2-pentenal are produced from the action of residual enzymes so that, especially at low drying temperatures, their concentration is proportional to the residual humidity of the sample [45]. From these studies, it could be inferred that the different contents of hexanal and 2-methyl-2-pentenal in sour meat fermented from goose meat versus pork could be linked to different activity of residual enzymes, in turn leading to variable extents of lipid oxidation in the final product [46].…”
Section: Discussionmentioning
confidence: 99%
“…Elmore et al [55] reported that PUFAs content in meat positively correlates with aldehyde content. Hexanal and pentanal are the products of oxidative degradation of linoleic acid, which provide fresh grass flavor and roasted nut aroma, respectively [56]. Linoleic acid can also be oxidized to form (E) -2-heptanal and (E) -2-octenal, which have fresh cucumber and fruit flavors.…”
Section: Effect Of Different Processing Methods On the Flavor Of Bts ...mentioning
confidence: 99%
“…It showed that the Maillard reaction intensity was higher in deep-fried meat than in pan-fried and baked meat, which is consistent with the chromaticity results. Furan compounds are formed from a variety of sources, such as from the oxidation of α-linolenic acid, γ-linolenic acid [56], and linoleic acid [71]. Sulfur compounds are formed by the degradation of thiamine [54] and have an onion/garlic odor.…”
Section: Effect Of Different Processing Methods On the Flavor Of Bts ...mentioning
confidence: 99%